The Role of Endocrine Disruptors and Environmental Chemicals in Causing Cancer: Focusing on Genetic and Epigenetic Mechanisms - Singh, Amit Kumar; Choudhary, Ranjay Kumar; Tiwari, Vikas; Kondaveeti, Suresh Babu; Kaur, Jappreet; Garg, Vivek Kumar; Sharma, Bunty; Aggarwal, Vaishali; Buttar, Harpal Singh (Scripta Medica, 2026)
Endocrine-disrupting chemicals (EDCs) and environmental pollutants are ubiquitous and increasingly linked to the aetiology of cancer. This review synthesises existing evidence on the carcinogenic potential of EDCs, including bisphenols, phthalates, pesticides, heavy metals and persistent organic pollutants, with a focus on genetic and epigenetic pathways. The molecular mechanisms by which these chemicals induce carcinogenesis, including DNA damage, chromosomal aberrations, dysregulation of oncogenes and tumour suppressor genes and alterations in DNA repair was critically accessed. Epidemiological research emphasises epigenetic changes, including aberrant DNA methylation, histone modifications and deregulated non-coding RNA expression, which mediate long-term and potentially transgenerational effects of exposure. The interplay among endocrine signalling, oxidative stress, inflammation and epigenetic reprogramming is discussed in relation to hormone-dependent and hormone-independent cancers. Epidemiological, in vivo and in vitro experimental evidence, together with high-throughput omics data, were integrated to strengthen mechanistic plausibility. This review identified important research gaps, including low-dose and mixture effects, timing of exposure and population-wide vulnerability and provides future directions for risk assessment and regulatory policy. Greater insight into the genetic and epigenetic effects of EDCs is needed to advance cancer prevention and inform evidence-based community health interventions.
Keywords: Endocrine disruptors; Neoplasms; Carcinogenesis; Epigenomics; Toxic; Metals